Sekuriti makanan dalam pembangunan negara - Ahmad Zubir Ibrahim (Sintok : Penerbit Universiti Utara Malaysia, 2022)
On food security in Malaysia.
Dr. Nurhafilah Musa/ Pensyarah Fakulti Undang-Undang/ hafilah@ukm.edu.my/ Emel/ OC/ Bookline Services
Includes bibliographical references and index. (135-150 pages)
Keywords: Food security -- Government policy -- Malaysia; Food security -- Religious aspects -- Islam; Food supply -- Government policy -- Malaysia